Epidemiology of Dupuytren’s Disease and Sociodemographic Factors Related to it Among Chronic Diabetic Patients - Aleena Kalsoom, Sadia Iftikhar, Farooq Islam, Tehreem Iqbal, Namra Sarwar, Arooj Malik, Asim Raza, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Dupuytren’s disease(DD) is characterized by progressive idiopathic fibrosis of the hand palm and the formation of nodules & contractures. Its prevalence ranges from 3 to 42% worldwide. Aim: To assess Dupuytren’s disease’s prevalence, severity and its association with different demographic factors. Study design: Analytical, Cross-sectional study done using Non-probability convenient sampling. Method: This study was conducted on 424 diabetic patients of age between 40 and 80. A questionnaire was used to assess different sociodemographic factors among them. Tubiana classification & tabletop test was used to assess the severity of the disease. Chi-square test was applied to find out the p-value for the association between variables. Results: About 9% of total participants were affected by DD. Most of the affected people were in the nodular stage or stage 1.There was a significant relationship found between DD and different factors like age group (p=<0.01),Family history of DD(p=<0.01), and previous hand injury (p=<0.01) Practical implication: This study provides us the baseline risk factors leading to the disease for better future interventions. Treatments gets easier when we reach the cause. Because nowadays the widely available treatment is surgical excision which is not a good option for everyone. Also there is a dearth of research on this emerging hand disability caused by diabetes that’s why this research is being conducted Conclusions: The results showed high prevalence of DD in diabetic patients with old age, positive family history of DD disease and previous hand injury. Therapeutic studies are required for the betterment of society and to prevent the disease from causing disability. Keywords: Contractures, Dupuytren’s disease, Dupuytren’s nodules, diabetes, personal factors, Family history.